Infection with Helicobacter Pylori and the Risk of Iron Deficiency Anaemia - Younas Ahmad, Ahmed Jamal Chaudhary, Muhammad Afzal, Abdul Moiz Bhatti, Muhammad Aleem Uddin, Sultan Zeb Khan, Sana Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Helicobacter pylori (H. pylori) is a globally prevalent infection that has been implicated in iron deficiency anemia (IDA) due to its effects on gastric physiology and iron absorption. IDA is a common micronutrient deficiency with significant health implications, especially in developing countries. Objective: To determine the frequency of iron deficiency anemia among patients infected with Helicobacter pylori and explore its association with demographic and clinical variables. Material and Methods: This cross-sectional study was carried out at Gastroenterology Department, Jinnah Medical College and Teaching Hospital, Peshawar, from July 2022 to March 2023. A total of 361 patients diagnosed with Helicobacter pylori infection via stool antigen testing were included. Data collected comprised demographic variables such as age, gender, socioeconomic status, smoking habits, and a history of gastrointestinal (GI) bleeding or ulcers. The diagnosis of iron deficiency anemia (IDA) was based on hemoglobin levels, defined as <13 g/dL in males and <12 g/dL in females. Statistical analysis was performed using SPSS, with significance set at p ≤ 0.05. Results: Mean age of participants was 43.60 ± 15.143 years while the mean hemoglobin was 12.48 ± 2.212 g/dL. 137 (38%) patients were found to have IDA and IDA was seen most frequently (45.6%) in age group 41 – 50 years. There were no statistically significant associations with IDA and age (p = 0.378), gender (p = 0.068), socioeconomic status (p = 0.866), GI bleeding or ulcers (p = 0.442) or smoking (p = 0.773). Conclusion: IDA is common in H. pylori infected patients and necessitates standard screening and timely management. More work is needed to understand the mechanism and long term consequences. Keywords: Helicobacter pylori, iron deficiency anemia, prevalence, risk factors, gastric infection, hemoglobin.